2021
DOI: 10.1182/bloodadvances.2021005076
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of cardiac abnormalities in pediatric patients with sickle cell anemia and effect of hydroxyurea therapy

Abstract: Cardiac abnormalities such as left ventricular hypertrophy, dilation and pulmonary hypertension in sickle cell anemia, have been previously described. Hydroxyurea, a disease modifying therapy for sickle cell anemia, has been used for several decades. Longitudinal assessment of echocardiographic abnormalities in children and young adults with sickle cell anemia on hydroxyurea therapy is lacking. In this retrospective study, we aim to determine the prevalence of echocardiographic abnormalities in children and yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
0
13
0
1
Order By: Relevance
“…More recently the results of a retrospective longitudinal analysis of echocardiograms in patients with SCD, the authors found a high prevalence of LVH among patients on hydroxyurea, with higher prevalence among those treated for less than a year than those who had been treated longer. 31 Further in the same study, analysis of serial echocardiogram reports showed that left ventricular dilation and hypertrophy improved significantly with hydroxyurea treatment, with a negative correlation between the treatment duration and left ventricular volume and mass. 31 …”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…More recently the results of a retrospective longitudinal analysis of echocardiograms in patients with SCD, the authors found a high prevalence of LVH among patients on hydroxyurea, with higher prevalence among those treated for less than a year than those who had been treated longer. 31 Further in the same study, analysis of serial echocardiogram reports showed that left ventricular dilation and hypertrophy improved significantly with hydroxyurea treatment, with a negative correlation between the treatment duration and left ventricular volume and mass. 31 …”
Section: Discussionmentioning
confidence: 78%
“… 31 Further in the same study, analysis of serial echocardiogram reports showed that left ventricular dilation and hypertrophy improved significantly with hydroxyurea treatment, with a negative correlation between the treatment duration and left ventricular volume and mass. 31 …”
Section: Discussionmentioning
confidence: 78%
“…Published pediatrics TRV data mostly precede the BABY‐HUG trial, whereby evidence has since suggested prolonged hydroxyurea therapy could lead to cardiac remodeling reversal. An elevated baseline TRV at 37% dropped to 11% after hydroxyurea 23 . Similarly, in a large retrospective study of 630 children, mean TRV declined significantly and only half had an elevated TRV on repeat assessment, with no discernible explanation, although it is possible that there could have been improved adherence to therapies 32 .…”
Section: Discussionmentioning
confidence: 99%
“…22 ECHO findings included left ventricle dilation, left ventricle hypertrophy, coronary artery dilation, PFO, and physiological valvular insufficiency, consistent with an earlier report. 23 Coronary artery dilation is common in SCD and associated with left ventricular hypertrophy. 24 A higher incidence of left coronary artery dilation is described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation